Book Reviews. Issue 3 (1st September 2019) - Zhou, Min; Rose, Phil; Thomas, Matt; Strate, Lance; Morrison, James C.
Marshall McLuhan's Mosaic: Probing the Literary Origins of Media Studies, Elena Lamberti (2012)Toronto: University of Toronto Press, 320 pp., ISBN-13 978-1-44264-013-9, h/bk, $79.50, p/bk, $31.84, Kindle, $29.19Understanding New Media: Extending Marshall McLuhan, Robert K. Logan (2016)New York: Peter Lang, 389 pp., ISBN-13 978-1-43311-126-6, h/bk, $141.65, p/bk, $24.69McLuhan Misunderstood: Setting the Record Straight, Robert K. Logan (2013)Toronto, Canada: Key Publishing House, 199 pp., ISBN-13 978-1-92678-052-8, p/bk, $18.69, Kindle, $8.99Feeling Mediated: A History of Media Technology and Emotion in America, Brenton J. Malin (2014)New York: New York University Press, 317 pp., ISBN 978-0-81476-057-4, p/bk, $25Harold Innis Reflects: Memoir and WWI Writings/Correspondence, William J. Buxton, Michael R. Cheney and Paul Heyer (eds), Foreword by Anne Innis Dagg (2016)Lanham, MD: Rowman & Littlefield, 253 pp., ISBN 978-1-44227-399-3, h/bk, $81.01, Kindle, $85.55The Return of the Moguls: How Jeff Bezos and John Henry Are Remaking Newspapers for the Twenty-First Century, Dan Kennedy (2018)Lebanon, NH: ForeEdge, an imprint of University Press of New England, 281 pp., ISBN 978-1-61168-594-7, h/bk, $29.95 ISBN 978-1-51260-178-7, e-book, $24.99